Mujeres esquivas and the paternal function - Cowling, Erin (My University, 2015)
Using the psychoanalytical concept of the paternal function, this article will explore the ways in which two similar plays, Lo que son mujeres by Francisco Rojas Zorilla and El desdén con el desdén by Agustín Moreto diverge in their endings, hinging on the function, or lack thereof, of the father figure.
Keywords: literature; theatre; psychoanalysis; comedia; Rojas Zorrilla; Moreto; mujer esquiva